Analisis Rantai Pemasaran Jambu Kristal (Studi Kasus Petani Jambu Kristal di Desa Neglasari) - Devi Nurul Faddhila Silitonga; Yannefri Bakhtiar; Amiruddin Saleh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Neglasari Village is one of the villages producing agricultural products where most of the community work as crystal guava farmers who plant it with a monoculture or intercropping system. Farmers produce crystal guava products to sell it to consumers in order to earn profits through marketing activities. This activity aims to analyze the marketing chain system of crystal guava and analyze the gross marketing margins on every marketing actors of crystal guava in Neglasari Village. The method used in this activity is the interview method and strengthened by literature review. Interview data were analyzed qualitatively descriptive. There are three marketing chains for guava crystal that farmers can choose from, that is selling directly to consumers, selling through Poktan or Gapoktan, and selling through collectors (middlemen). From that three channels, the marketing chain by selling directly to consumers has been proven to provide the highest gross marketing margin to farmers while the lowest margin is obtained if it is through middlemen. This report is expected to be a policy reference in improving the marketing system of guava crystals in Neglasari Village on effort to improve the welfare of marketing actors, especially farmers as producers. Key words: crystal guava, marketing chain, margin